Implementasi Kebijakan Tentang Pencegahan dan Penanggulangan Terhadap Penyalahgunaan Narkoba di Kabupaten Aceh Tenggara (Qanum Kabupaten Aceh Tenggara Nomor 4 Tahun 2016) - Oktaviani, Tiya; Marisa Sihombing, R Sally (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Southeast Aceh District is one of the places for drug trafficking, seeing the development of drug cases in Southeast Aceh The Southeast Aceh District Head issued Qanum No 4 of 2016 as an effort to prevent and deal with drug abuse. This study aims to describe how the Policy for the Prevention of Eradication of Drug Abuse and Illicit Trafficking in Southeast Aceh District is implemented. The data obtained were analyzed using the implementation theory put forward by Van Meter and Van Horn, which includes standards and targets, resources, characteristics of implementing agents, communication, implementor dispositions, and the economic, social, and political environment. The results of this study indicate that the implementation of the Policy in Southeast Aceh District has not gone well.